COLCHICINE INDUCED MORPHOLOGICAL VARIATION IN MULBERRY VARIETY M5 - H. L. RAMESH; V. N. YOGANANDA MURTHY; MUNIRAJAPPA (The Bioscan, 2011)
Mulberry variety M5 is used for the induction of variation through colchicine treatment. Five different concentrations of aqueous colchicine [C22H25NO5 ] viz., 0.1% - 0.5% were used to treat the vegetative buds. Sprouting%, rooting% and plant height were decreased with a linear increase in the percentage of colchicine used. Increase in leaf area was observed at 0.4% (166.94 cm2 ) and 0.5% (165.20 cm2 ) when compared to control (155.41 cm2 ) plants. Thick, succulent and dark leaves were found associated with the increased leaf area. In the M2 generation, the variant exhibited decreased number of stomata/unit area (39.57) and increased number of chloroplast (18 – 22) were observed when compared to control (49.42 and 11 – 14). Yield of the treated plants (0.573kg/plant) were considerably increased. The plants are grown in full maturity in order to test their potential for use in a breeding programme oriented at producing lines with quantitative quality of leaves.